(untitled) (Res Medica, 2013)
How frequently in clinical practice do we have to treat the patient in respiratory distress? How frequently do we have to administer oxygen, and on what criteria do we do so? How frequently do such patients die, and how frequently do we claim their death as being inevitable? Woolmer (1956) states that respiratory inadequacy exists “when the gas exchange between the lungs and blood falls below that between the tissues and the blood : when external respiration cannot keep place with internal respiration ” . (17) Melville Arnott (1960) is more direct, stating that respiratory inadequacy is the preliminary stage of respiratory failure, namely, “that condition in which the amount of oxygen and carbon dioxide in the blood stream is altered by an abnormality of the respiratory system” . (23) Comroe et al. state specifically as the basic facts of respiratory inadequacy, hypoxaemia, CO2 retention, and respiratory acidosis. Previously the concept of respiratory inadequacy has had comparatively little attention in the numerous conditions involving the lungs, other than in the case of acute laryngeal obstruction. To quote Melville Arnott, “ too much emphasis has perhaps been placed on the effect of these conditions on cardiac function, and the resulting varied symptoms have been regarded as cardiovascular rather than respiratory ” .